Techno-economic Case for a Remote WiMAX Cell - Medeišis, A. (Elektronika ir Elektrotechnika, 2008)
This paper provides technical and economic analysis of deploying a stand-alone WiMAX cell in remote scarcely populated areas. First it considers the technical aspects of sufficient capacity as well as range, and concludes with reviewing the economic viability using NPV method. The analysis shows that such deployment would have to cope with significant challenges, both technically in terms of maximum range and economically in terms of risk of negative return on investments in the short term. Ill. 2, bibl. 8 (in English; summaries in English, Russian and Lithuanian).